Legal Protection for Household Assistants as Victims based on Law Number 23 of 2004 on The Elimination of Domestic Violence - Mila Cahyawati; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2025)
This study is based on the case of household assistants, or ART, who often suffer violence that is part of household violence itself, even though in its terminology the perpetrators and victims are part of the household. In this case, a household assistant is a person who is outside the family circle but is often the target of household violence incidents. This research aims and will focus on legal protection for household assistants who are often victims of household violence itself, which will be analysed legally based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The research method used is a doctrinal approach and normative legal; the researcher wants to provide a broad and brief description of the legal protection for household assistants who are victims of household violence from the existing law regulations. From the author's in-depth study, it was found that the results of the study were to provide a reference for household assistants in handling the resolution of domestic violence found and become a general description of the actions and legal protection related to violent acts against household assistants in the scope of the household. As well as emphasizing the position of household assistant in the scope of the household and providing legal certainty for household assistants as victims of domestic violence.